Evaluating possible ‘next day’ impairment in insomnia patients administered an oral medicinal cannabis product by night: a pilot randomized controlled trial - Anastasia Suraev; Danielle McCartney; Nathaniel S. Marshall; Christopher Irwin; Ryan Vandrey; Ronald R. Grunstein; Angela L. D’Rozario; Christopher Gordon; Delwyn Bartlett; Camilla M. Hoyos; Iain S. McGregor (Psychopharmacology, 2024)
Cannabis and its major constituents, Δ 9 -tetrahydrocannabinol (THC) and cannabidiol (CBD), are being widely used to treat sleep disturbances. However, THC can cause acute cognitive and psychomotor impairment and there are concerns that driving and workplace safety might be compromised the day after evening use. Here, we examined possible ‘next day’ impairment following evening administration of a typical medicinal cannabis oil in adults with insomnia disorder, compared to matched placebo. This paper describes the secondary outcomes of a larger study investigating the effects of THC/CBD on insomnia disorder. Twenty adults [16 female; mean (SD) age, 46.1 (8.6) y] with physician-diagnosed insomnia who infrequently use cannabis completed two 24 h in-laboratory visits involving acute oral administration of combined 10 mg THC and 200 mg CBD (‘THC/CBD’) or placebo in a randomised, double-blind, crossover trial design. Outcome measures included ‘next day’ (≥9 h post-treatment) performance on cognitive and psychomotor function tasks, simulated driving performance, subjective drug effects, and mood. We found no differences in ‘next day’ performance on 27 out of 28 tests of cognitive and psychomotor function and simulated driving performance relative to placebo. THC/CBD produced a small decrease (-1.4%, p =.016, d =-0.6) in accuracy on the Stroop-Colour Task (easy/congruent) but not the Stroop-Word Task (hard/incongruent). THC/CBD also produced a small increase (+8.6, p =.042, d =0.3) in self-ratings of Sedated at 10 h post-treatment, but with no accompanying changes in subjective ratings of Alert or Sleepy ( p’s >0.05). In conclusion, we found a lack of notable ‘next day’ impairment to cognitive and psychomotor function and simulated driving performance following evening use of 10 mg oral THC, in combination with 200 mg CBD, in an insomnia population who infrequently use cannabis.